Allometry and Distribution of Nitrogen in Natural Plant Communities of the Tibetan Plateau - Li, Xin; Li, Mingxu; Xu, Li; Liu, Congcong; Zhao, Wenzong; Cheng, Changjin; He, Nianpeng (Frontiers in Plant Science, 2022)
Nitrogen (N) is an important element for most terrestrial ecosystems; its variation among different plant organs, and allocation mechanisms are the basis for the structural stability and functional optimization of natural plant communities. The nature of spatial variations of N and its allocation mechanisms in plants in the Tibetan Plateau—known as the world’s third pole—have not been reported on a large scale. In this study, we consistently investigated the N content in different organs of plants in 1564 natural community plots in Tibet Plateau, using a standard spatial-grid sampling setup. On average, the N content was estimated to be 19.21, 4.12, 1.14, and 10.86 mg g–1 in the leaf, branch, trunk, and root, respectively, with small spatial variations. Among organs in communities, leaves were the most active, and had the highest N content, independent of the spatial location; as for vegetation type, communities dominated by herbaceous plants had higher N content than those dominated by woody plants. Furthermore, the allocation of N among different plant organs was allometric, and not significantly influenced by vegetation types and environmental factors; the homeostasis of N was also not affected much by the environment, and varied among the plant organs. In addition, the N allocation strategy within Tibet Plateau for different plant organs was observed to be consistent with that in China. Our findings systematically explore for the first time, the spatial variations in N and allometric mechanisms in natural plant communities in Tibet Plateau and establish a spatial-parameters database to optimize N cycle models.